The Development of Brand, Packaging and Label of Santol Sauce by Participatory Action Research of Baan Ngew Rai Organic Farming Community Enterprise, Mueang Lop Buri District, Lop Buri Province - Puangpejara, Kulchalee; Puangpejara, Somporn; Jangsawang , Nantana; Boonthanom, Nuchjara (Community and Social Development Journal, 2021)
The purposes of this research were to: 1) study the state and problems of santol sauce product by participatory action research of Baan Ngew Rai Organic Farming Community Enterprise, Mueang District, Lop Buri Province; and 2) develop santol sauce product by of Baan Ngew Rai Organic Farming Community Enterprise to be the outstanding identity. The samples, selected by purposive sampling, comprised 1) executives of government agency and a marketing academic staff, totaled nine persons, 2) five community leaders in study area, 3) 16 members affiliated to Baan Ngew Rai Organic Farming Community Enterprise and a group of 14 farmers who produce santols in Ngew Rai and Talung Sub-district, and 4) 400 customers chosen by accidental sampling. The Mixed Method Research (MMR) was employed for data collection. This included observation, in-depth interviews, training, focus group technique, and questionnaires, The quantitative data were systematically analyzed by descriptive statistics (percentage, mean and standard deviation). The qualitative data were analyzed by content analysis. The findings revealed that the brand, packaging, and label of santol sauce product of Baan Ngew Rai Organic Farming Community Enterprise had serious problems as follows: 1) the product's brand was not satisfied with customers, no distinctive feature to attract their attention and remembrance, 2) the packaging was quite problematic as it was a wide mouth glass bottle with a screw cap which was inconvenience for product users and transportation, and 3) the font size on the label was small, information including the ingredients and directions were not complete as require by the Ministry of Public Health. With regards to the research results above, the members and involved parties had solved the problems as follows:1) developed the brand by improving the product logo and slogan to make it easy to remember and be interest, 2) changed the bottle cap from a screw cap to a squeeze cap to be easy and convenient for consumers, and 3) enlarged the font size on the label and add more information of ingredients direction, manufactured date, and expiry date as specified by the Ministry of Public Health.